INVESTIGATING ENGLISH TEACHERS’ DIGITAL LITERACY IN THE CONTEXT OF ONLINE LEARNING - Hanan, Ahmad; Firman, Edi; Putri, Ayi Nurfazriah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
In particular cases, teachers still strugle to find valid content of material in the internet, it is because teachers lack comprehending about digital literacy. While education policy has fliped the teaching learning process to online learning based, the use of technology has increased significantly. As a result the ability to search, allocate and evaluate the information in the internet is a crucial thing to be acquired by the teachers. Therefore, this research aims to reveal teachers’ levels of digital literacy and to find out what support teachers need to increase their digital literacy. This research was qualitative descriptive, gathering data through the interview with six teachers at two senior high school in Mataram. The result of the study showed that teachers have a medium level of digital literacy. Teachers’ digital literacy levels involve four aspect of digital literacy competencies which is the ability to use digital tools, know its purposes,  and able to operate it even in a complex way. In addition, the researcher also found the support that can increase teachers’ digital literacy include; (a)  teachers’ development where teachers need to involve themselves in training and self development, and (b) the facilities/resources such as computer, laptop and internet connection.